2018
DOI: 10.1103/physrevfluids.3.024605
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent statistics and intermittency enhancement in coflowing superfluidHe4

Abstract: The large scale turbulent statistics of mechanically driven superfluid 4 He was shown experimentally to follow the classical counterpart. In this paper we use direct numerical simulations to study the whole range of scales in a range of temperatures T ∈ [1.3, 2.1] K. The numerics employ selfconsistent and non-linearly coupled normal and superfluid components. The main results are that (i) the velocity fluctuations of normal and super components are well-correlated in the inertial range of scales, but decorrela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 33 publications
9
38
0
Order By: Relevance
“…in Ref. 2,13,18,20 ). Here α is the dimensionless mutual friction parameter related 1 to γ 0 as αρ s κ = (1 + α 2 )γ 0 , L is the vortex line density.…”
Section: Qualitative Analysis Of Anisotropic Counterflow Turbulencementioning
confidence: 99%
See 2 more Smart Citations
“…in Ref. 2,13,18,20 ). Here α is the dimensionless mutual friction parameter related 1 to γ 0 as αρ s κ = (1 + α 2 )γ 0 , L is the vortex line density.…”
Section: Qualitative Analysis Of Anisotropic Counterflow Turbulencementioning
confidence: 99%
“…The detailed study of the statistics of the coflow was reported in Ref. 20 . Other parameters of the simulations were chosen based on dimensionless numbers: i) the Reynolds numbers Re j = ∆u ν j k 0 , ii) the turbulent intensity U ns ∆u , and iii) the dimensionless cross-over scale…”
Section: A Simulation Parameters and Numerical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In the opposite limit T → T λ , the superfluid fraction vanishes and the classical behavior discussed above is recovered. More interesting is the intermediate case where the two fluid densities and viscosities are similar, at T ≈ 1.9 K. In this case, in the absence of a mean counterflow, the two velocity fields are tightly coupled even at the smallest flow scales [23]. Hence, S n ≈ S s and Ω n ≈ Ω s , and the clustering behavior predicted by eq.…”
mentioning
confidence: 96%
“…As in ref. [23], the latter is estimated as Ω 2 0 = |ω s | 2 /2, where ω s = ∇ × u s is the superfluid vorticity, and · denotes a space average. The two velocity fields are stirred by independent large-scale Gaussian random forces Φ s (x) and Φ n (x) of unit variance.…”
mentioning
confidence: 99%